Growth responses of Mucuna bracteata to application of abscisic acid / Siti Nor Ayuni Awang Noh - Awang Noh, Siti Nor Ayuni (Faculty of Plantation and Agrotechnology, 2015)
The experiment on growth inhibition of Mucuna bracteata was conducted at the back of greenhouse at Universiti Teknologi MARA (UiTM) Jasin, Malacca. Leguminous cover crops such as M. bracteata are important plants, especially in oil palm plantations. The fast and vigorous growth of M. bracteata may compete with the main crop for nutrient, water, space and air. The objective of this study was to inhibit the vigorous growth of M. bracteata by using abscisic acid (ABA). This study was also aimed to determine the best rate of ABA that should be applied on M. bracteate to suppress its growth. The parameters measured to indicate the inhibition of Mucuna were length of internode, diameter of stem, number of shoot, leaf area and relative chlorophyll content. There were five treatments in this experiment and each treatment was replicated four times. Data analyses were carried out by using SPSS. The result showed that treatment with 20 mg/l ABA was sufficient to inhibit the growth of M. bracteata in terms of internode length, relative chlorophyll content but encouraged more branching from the main vines.